2004
DOI: 10.1016/s0212-6567(04)78907-6
|View full text |Cite
|
Sign up to set email alerts
|

Enfermedad funcional tiroidea en la población de edad avanzada

Abstract: FTP is more prevalent among the elderly than in the population as a whole, with predominance of hypothyroidism, subclinical pathology and among women. In terms of pathology traditionally linked to thyroid malfunction, few differences were found between the population affected with FTP and those not affected. Primary care doctors are important in reducing under-diagnosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
1
1
2

Year Published

2009
2009
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 16 publications
2
1
1
2
Order By: Relevance
“…Díez et al [26] described a prevalence of subclinical hypothyroidism around 1.02% in healthy ambulatory subjects aged from 60 to 84 years in an urban community in Madrid (Spain) and a prevalence of subclinical hyperthyroidism of 6.12%. In another study, conducted in Terrassa (Catalonia), also in older healthy ambulatory subjects, the prevalence of total hypothyroidism (overt, subclinical, and previously diagnosed) was 10.9% and that of thyroid dysfunction in general 13% [27]. These data differ from our general results, probably due to the different ages of the subjects studied and other environmental factors.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…Díez et al [26] described a prevalence of subclinical hypothyroidism around 1.02% in healthy ambulatory subjects aged from 60 to 84 years in an urban community in Madrid (Spain) and a prevalence of subclinical hyperthyroidism of 6.12%. In another study, conducted in Terrassa (Catalonia), also in older healthy ambulatory subjects, the prevalence of total hypothyroidism (overt, subclinical, and previously diagnosed) was 10.9% and that of thyroid dysfunction in general 13% [27]. These data differ from our general results, probably due to the different ages of the subjects studied and other environmental factors.…”
Section: Discussioncontrasting
confidence: 95%
“…If subjects over 60 with diagnosed thyroid disease are also considered, the total prevalence (diagnosed ? undiagnosed) of thyroid dysfunction in this group was 13.61%, similar to that reported by Sender Palacios et al [27]. Women constituted 53.12% of these subjects and 46.87% were men.…”
Section: Discussionsupporting
confidence: 91%
“…The SCH prevalence of 9.7% is in good agreement with the 9.2-9.5% reported so far (1, 6). As previously published (10, 11), the mean TSH level increased with aging to reach a prevalence of a diagnosed SCH prevalence of 11.7% (8.4% for <60y group), in agreement with the 10.4-14.5% found in European citizens ≥60y (12, 36). Unfortunately, given the context of the study, which was conducted in current care, we were not able to perform follow up measurements of thyroid function markers or to follow evolution of the diagnosed SCH prevalence in our cohort.…”
Section: Discussionsupporting
confidence: 89%
“…The prevalence of thyroid dysfunction found in the present study was similar to that reported in other studies performed in aged population in our country, which ranged from 4 to 13%. [14][15][16][17][18][19][20] Although it has been generally admitted that the prevalence of thyroid dysfunction in the elderly is higher in hospitalized and institutionalized patients than in general population, 21-24 these findings have not been confirmed in elderly population in our area. 18 It is remarkable that prevalence of thyroid dysfunction found in Spanish populations has been lower than that reported in American population.…”
Section: Discussionmentioning
confidence: 98%